Proceeding 2nd international conference of translational medicine and health sciences in conjunction with 4th Java international nursing conference 2018 : "creating a better future of health care : partnership in research, education and clinical care", Patra Semarang Hotel & Convention, Central Java, Indonesia 14-15 September 2018 (Faculty of Medicine, Diponegoro University, 2018)
penelitiian, pendidikan dan klinik perawatan